2019
DOI: 10.1136/bmjopen-2019-030386
|View full text |Cite
|
Sign up to set email alerts
|

Association between participation in the Families First Home Visiting programme and First Nations families’ public health outcomes in Manitoba, Canada: a retrospective cohort study using linked administrative data

Abstract: ObjectiveTo determine whether the Families First Home Visiting (FFHV) programme, which provides home visiting services to families across Manitoba, is associated with improved public health outcomes among First Nations families facing multiple parenting challenges.DesignRetrospective cohort study using population-based administrative data.SettingManitoba, Canada.ParticipantsFirst Nations children born in Manitoba in 2003–2009 (n=4010) and their parents enrolled in FFHV compared with non-enrolled families with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…EDI data collected in countries across the globe, such as Canada, Australia, Ireland, and Ethiopia, have been used to implement and evaluate programs meant to improve children’s developmental health at school entry [ 16 , 17 , 18 , 67 ]. One of the most important and ubiquitous programs put in place to help support early child development is preschool.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…EDI data collected in countries across the globe, such as Canada, Australia, Ireland, and Ethiopia, have been used to implement and evaluate programs meant to improve children’s developmental health at school entry [ 16 , 17 , 18 , 67 ]. One of the most important and ubiquitous programs put in place to help support early child development is preschool.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the earlier a child exited the program, the more vulnerable they were in all five developmental domains of the EDI [ 19 ], suggesting the program was effective at improving children’s developmental health; however, a multivariate analysis found no overall difference among the study groups in terms of EDI outcomes. Many other countries have attempted to use early at-home interventions to improve developmental outcomes for marginalized communities before entering preschool [ 18 , 72 ]. A study by Enns et al [ 18 ] focused specifically on the Families First Home Visiting (FFHV) program available to indigenous populations in Manitoba.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Resultados progressivos e contínuos são importantes e que quanto mais tempo as crianças ficam expostas às intervenções com VD, mais elas conseguem atingir os marcos do desenvolvimento infantil (DUFFEE et al, 2017). O sucesso no desenvolvimento infantil pode ser pertinente pela redução nos riscos de resultados psicossociais e de aprendizagem negativos (SALVY et al, 2017 (ENNS et al, 2019;GRACE et al, 2019).…”
Section: Discussionunclassified